Analisis Performa Website Pada Implementasi MERN Stack Dengan MySQL Dalam Pengembangan HairHub - Danang Rifai; Sri Huning Anwariningsih; Astri Charolina (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2024)
HairHub is an information center website for barbershop and salon owners and users. Based on observations, there is a problem related to the length of time the page loads. This study aims to analyze and improve the performance of the HairHub website which is implemented using MERN Stack (MongoDB, Express.js, React.js, Node.js) with MySQL as a database. This study focuses on analyzing the loading speed of website pages using two main performance analysis tools, namely Google PageSpeed Insights and GTmetrix. The evaluation results show that optimization contributes significant improvements in various aspects, namely the performance score in Google PageSpeed Insights increased from an average of 75 to almost 100, while in GTmetrix it increased from an average of 65 to almost 80. Refactoring the program code contributes to an increase in the structure score in GTmetrix from 73-78 to 91-92. Accessibility score on Google Page Speed Insights increased from 86 to 95, and best practice score from 89 to 96. However, the SEO score remained stable at 83. This study shows that optimization successfully improved HairHub website performance and quality with faster page load time and easier navigation.